PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS IV SD NEGERI 47 KOTO TUO KECAMATAN KOTO TANGAH PADANG - Novriadi, Novriadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstrackThis research was conducted due to the fourth grade studen`slow learning achievement at SD Negeri 47 Koto Tuo Kecamatan Koto Tangah Padang. The aim of this research was to describe the improvement of the student`s learning achievement in Social Scince by using Problem Based Learning model in the fourth grade of  SD  negeri   47 Koto Tuo Kecamatan Koto Tangah Padang.  This  was  a classroom action research   which applied qualitative and quantitative approaches. The result of the research indicated that the student`s learning achievement improved from 76,25 in the first cycle into 90,50 in the second cycle. Hence, the use of Problem Based Learning model could improve the students` learning achievement in Social Science in the fourth grade of SD Negeri 47 Koto Tuo Kecamatan Koto Tangah Padang. keywords: Students, Social, Scince, Problem, Based Learning Model.